Florida's Property Tax Reform: Local Government Impacts of the Proposed Constitutional Change - Rodney L. Clouser (EDIS)
FE707, a 7-page fact sheet by Rodney L. Clouser, is part of the Florida’s Property Tax Reform series. It reports changes in the estimated cost of the proposed constitutional amendment and informs about the impact of proposed changes to the Florida Constitution that will be voted on by the state citizens on January 29, 2008. Includes references. Published by the UF Department of Food and Resource Economics, January 2008.